Some pharmacopoeial tests for a folklore herb Cordyline fruticosa (L.) A. Chev. and monographic standards with antioxidant assay thereof (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2025)
Cordyline fruticosa (L.) A. Chev. also recognised as a good luck plant, it is commonly used to treat fever, asthma, rheumatic bone pains, smallpox, joint pain, bleeding skin eruptions, and as an abortifacient. In this study, standardisation tests like physicochemical and HPTLC were carried out on leaves of the plant as per Pharmacopoeia. Results of the micro powder study showed fragments of mesophyll parenchymatous tissue embedded with brownish materials, oil globules and bundles of acicular crystals. The mixture of toluene, ethyl acetate, and formic acid (8.5:3.0:0.5v/v) was used as a mobile phase to obtain the HPTLC fingerprint profile. Photo-documentation of methanolic leaf extract, when observed under UV 254 nm, revealed 13 bands, 11 bands under UV 366 nm, and densitometric scanning revealed 13 peaks at 520 nm. By HPLC, 12 peaks were obtained when a methanol and water (60:40) mixture was used as the mobile phase. The antioxidant property of the methanolic leaf extract of C. fruticosa was analysed by ABTS and DPPH radical scavenging techniques. The DPPH radical scavenging method showed that the IC50 values of C. fruticosa and standard ascorbic acid were 70.317±0.51849 and 11.13±1.29179 μg/mL, respectively. The IC50 values of C. fruticosa and standard trolox were found 47.2348±1.56651 and 37.6146±1.24248 μg/mL, respectively when it was analysed by the ABTS radical scavenging method. The total flavonoid and total phenolic content of the methanol extract of C. fruticosa was determined to be 0.7298±0.00162 µg QE/mg and 34.92±0.01808 µg GAE/mg, respectively.